Lack of butyrate is associated with induction of Bax and subsequent apoptosis in the proximal colon of guinea pig - Hass, R; Busche, R; Luciano, L; Reale, E; Engelhardt, W V (Gastroenterology (New York, N.Y. 1943), 1997)
Butyrate stimulates proliferation and suppresses differentiation in normal colonic epithelial cells. Because the involved intracellular signaling mechanisms are unclear, this study investigated certain molecular effects of butyrate. Tissue sheets from guinea pig proximal colon were incubated in Ussing chambers in the presence and absence of butyrate. Colonic tissues were examined by scanning and transmission electron microscopy, DNA laddering, Western blots, and immunohistochemistry. After incubation of the colonic mucosa for 150 minutes without butyrate, morphological studies showed massive apoptosis of colonocytes. Simultaneously, these colonocytes exhibited a significant oligonucleosomal DNA fragmentation. In contrast, addition of physiological concentrations of butyrate (10 mmol/L) to colonic sheets showed no detectable DNA fragmentation within 150 minutes. Western blot analysis showed little if any difference in the level of Bcl-2 expression in colonocytes incubated with or without butyrate up to 150 minutes. In contrast, expression of Bax proteins continuously increased after 45 minutes without butyrate and reached a fivefold induction after 150 minutes compared with cells incubated in the presence of butyrate. Moreover, immunohistochemistry using an anti-Bax antibody system showed enhanced labeling of the epithelial colonocytes in the absence of butyrate. Removal of butyrate induces increased expression of Bax proteins paralleled by rapid apoptosis of colonocytes in vitro.